The synergistic effect of temperature, H2S/CO2 partial pressure and stress toward corrosion of X80 pipeline steel. (April 2023) - Huang, Xiaoguang; Zhou, Longchi; Li, Yukun; Du, Zhongzhe; Zhu, Qihui; Han, Zhongying
Highlights: The partial pressure ratio H2 S/CO2 dominated the corrosion process and corrosion mechanism of X80 in H2 S/CO2 coexistence. The corrosion rate reaches its maximum near 100 °C in the simulated temperature range (50 °C–150 °C). X80 steel has a higher stress corrosion cracking resistance under the H2 S/CO2 coexistence environment. Abstract: In this work, the H2 S / CO2 coexistence environment was simulated in a high-temperature and high-pressure reactor. The influence of H2 S/CO2 partial pressure (0/1.2, 0.7/1.2 and 2.0/1.2 MPa), temperature (50, 100 and 150 °C) and applied stress (30%, 70% and 90% σ s ) on the corrosion rates of natural gas pipeline steel X80 was investigated by the weight loss measurements combined with the SEM, EDS and XRD techniques. The results show that the corrosion of X80 steel under pure CO2 condition is much more serious than that under H2 S/CO2 coexistence. The corrosion stability of amorphous film can be improved by the formation of amorphous Cr (OH)3 in the presence of H2 S, which provides better surface protection than in the pure CO2 environment. The corrosion of X80 steel in H2 S/CO2 coexistence is dominated by H2 S corrosion and the corrosion rates increase with the increase of H2 S partial pressure. The corrosion rate firstly increases with the increase of temperature, and the highest corrosion rate occurs near 100 °C under the existing experimental conditions. After that, the corrosion rate began to decrease. The applied stress significantly affects the corrosion rate, and high stress speeds up the corrosion process of X80 steel in the H2 S/CO2 coexistence environment.